2012
DOI: 10.1186/1471-2407-12-74
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of ErbB-2/HER2 nuclear expression in breast cancer

Abstract: BackgroundThe biological relevance of nuclear ErbB-2/HER2 (NuclErbB-2) presence in breast tumors remains unexplored. In this study we assessed the clinical significance of ErbB-2 nuclear localization in primary invasive breast cancer. The reporting recommendations for tumor marker prognostic studies (REMARK) guidelines were used as reference.MethodsTissue microarrays from a cohort of 273 primary invasive breast carcinomas from women living in Chile, a Latin American country, were examined for membrane (MembErb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 37 publications
2
29
0
Order By: Relevance
“…MErbB-2, NErbB-2, and NStat3 were studied and scored as we reported. 13,50 The expression of PDCD4, mostly a nuclear protein in BC, 51,52 was studied by immunohistochemistry and scored on a 0 to 3 scale as described in Materials and Methods. Scores of 2+ and 3+ were considered positive (Supplementary Figure S6a).…”
Section: Mir-21 Induced By the Stat3/erbb-2 Transcriptional Complex Dmentioning
confidence: 99%
“…MErbB-2, NErbB-2, and NStat3 were studied and scored as we reported. 13,50 The expression of PDCD4, mostly a nuclear protein in BC, 51,52 was studied by immunohistochemistry and scored on a 0 to 3 scale as described in Materials and Methods. Scores of 2+ and 3+ were considered positive (Supplementary Figure S6a).…”
Section: Mir-21 Induced By the Stat3/erbb-2 Transcriptional Complex Dmentioning
confidence: 99%
“…Pretreatment patient staging was classified according to the system of the American Joint Committee on Cancer (AJCC; Singletary et al 2002) through the Elston and Ellis histological grading (Page et al 1995). TMAs were constructed as described earlier (Schillaci et al 2012).…”
Section: Patients and Tissue Microarraysmentioning
confidence: 99%
“…Immunofluorescence was performed as described previously (Schillaci et al 2012), using the mouse monoclonal anti-pStat3Ser727 (6E4) antibody (dilution 1:50 overnight at 4 8C; Cell Signaling). Slides were then incubated with an anti-mouse Alexa 488-conjugated antibody (1:1000, Molecular Probes).…”
Section: Immunofluorescence and Immunohistochemistry Analysis Of Tmasmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, both nuclear ErbB-2 and COX-2 were associated with reduced disease-free survival in patients receiving tamoxifen in the adjuvant setting (Dillon et al 2008). More recent clinical studies in a small cohort of primary invasive BCs revealed a role for nuclear ErbB-2 as an independent prognostic factor of poor clinical outcome in MErbB-2-positive tumors (Schillaci et al 2012). …”
Section: Clinical Significance Of Nuclear Erbb-2 As a Biomarker In Bcmentioning
confidence: 92%